The art of sustainable performance : a model for recruiting, selection, and professional development (2020)
“As a young man, it seemed that the American Billy Beane could beat anyone at any sport. As a natural, he was so much better than anyone he competed against, it almost seemed like he was playing a sport far easier than the one his opponents were playing. In his second year of high school, Billy Beane was both quarterback for the football team and point leader for the basketball team. It was as if he discovered talents in himself before his body was ready to do anything with them. For example, he was able to dunk a ball before his hands were even big enough to lift the ball with one hand. Billy was a typical example of an American teenager with many talents, including a major one: playing baseball” (Lewis 2003).